Interaction of Wildlife and People Residing near National Park Area - Dhakal, Devendra (Journal of Advanced Academic Research, 2017)
Interaction is the relationship between organisms for food, shelter and other needs. It may be positive or negative. There is strong interaction between wildlife and local people particularly at the national park and its adjoining area. Local people are responsible for a number of problems related to protected area management. The objective of this study was to assess the causes of interactions and find out the ways for park-people management. This study has been designed to reveal the intricate relationship among the wildlife and local people. The study applied cross-sectional design and used quantitative and qualitative approaches to collect data. Research instruments namely interview, questionnaire and observation were applied for this study. In any National Park in Nepalese context relation between wildlife and local people is positive and negative. Wildlife helps in promoting and maintaining greenery. It also helps in promoting tourism in the area. Journal of Advanced Academic Research, Vol. 3, No. 3, 2016, Page :100-104